Asymmetric Conjugate Addition of Alkylzirconocenes to Cyclopent-4-ene-1,3-dione Monoacetals - Rideau, Emeline; Mäsing, Florian; Fletcher, Stephen P. (Synthesis, 2015)
Copper-catalyzed asymmetric conjugate additions are powerful reactions that allow the formation of single-enantiomer building blocks in a few steps. However, highly enantioselective conjugate addition to five-membered-ring substrates is more challenging and is often neglected. Here, we report catalytic asymmetric 1,4-addition of alkylzirconocenes, formed in situ from readily available alkenes, to cyclopent-4-ene-1,3-dione monoacetals. Good to high enantioselectivities are observed and the procedure tolerates various functional groups.
Keywords: addition reactions; copper; asymmetric catalysis; organometallic reagents; acetals